1985
DOI: 10.1002/jnr.490140108
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the potassium‐induced stimulation of oxygen uptake in brain slices studied with cesium as a probe

Abstract: The potassium-induced stimulation of oxygen consumption in brain slices has a threshold value of 15-20 mM potassium, and it reaches its maximum at 35-50 mM. Although this phenomenon now has been known for almost 50 years, its physiological role remains undetermined. One reason for this may be that the high concentrations of potassium that are required for this response also have many other consequences, e.g., a depolarization of the cells, and that the different effects to some extent may mask each other. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The stimulation of oxygen uptake in brain slices by elevated [K + ] e is also accompanied by astrocytic cell swelling (Hertz and Kjeldsen, 1985). This finding further supports a correlation between K + -mediated stimulation of oxygen consumption and activation of the Na + , K + , 2Cl − cotransporter with its subsequent stimulation of Na + , K + -ATPase activity, because the cotransporter and the Na + ,K + -ATPase together mediate net uptake of 2K + plus 2Cl − into the cells (Figure 3), and the ion uptake, for osmotic reasons, is accompanied by entry of water and cell swelling.…”
Section: Brain Activation and Neuromodulators Increase Astrocytic Enementioning
confidence: 99%
“…The stimulation of oxygen uptake in brain slices by elevated [K + ] e is also accompanied by astrocytic cell swelling (Hertz and Kjeldsen, 1985). This finding further supports a correlation between K + -mediated stimulation of oxygen consumption and activation of the Na + , K + , 2Cl − cotransporter with its subsequent stimulation of Na + , K + -ATPase activity, because the cotransporter and the Na + ,K + -ATPase together mediate net uptake of 2K + plus 2Cl − into the cells (Figure 3), and the ion uptake, for osmotic reasons, is accompanied by entry of water and cell swelling.…”
Section: Brain Activation and Neuromodulators Increase Astrocytic Enementioning
confidence: 99%
“…1). The proposed sequence of events between stimulation of oxidative metabolism, increase in intracellular C 0 2 tension, intracellular alkalinization, and accumulation of Na+, together with either HC0: or C1-, in astrocytes might account for an apparently close correlation between stimulation s f oxygen consumption and swelling in brain slices during exposure to elevated concentrations of either potassium or cesium (Hertz and Kjeldsen 1985). Alternatively, glial swelling in brain slices might be due mainly to extracellular accumulation of neuronally released compounds like glutamate (see below).…”
Section: Carbsnf C Anhydresementioning
confidence: 96%
“…Early studies in Leif Hertz' career demonstrated that high levels of K + enhanced respiration in cultured astrocytes and acute brain slices, indicating a primary metabolic effect on respiration in astrocytes, not neurons, in living brain tissue (Hertz et al, 1973; Hertz & Kjeldsen, 1985). Peng, Hertz, and colleagues (Peng et al, 1994; Peng & Hertz, 1993) subsequently reported that increased extracellular [K + ] stimulated oxidative metabolism of glucose in glutamatergic neuronal cultures and astrocytic cultures and enhanced glucose utilization (measured as [ 14 C]DG phosphorylation) in cultured astrocytes.…”
Section: K+ Uptake Influences Astrocyte Metabolism and Signaling Path...mentioning
confidence: 99%